Mental health policy implementation in low- and middle-income countries: a realist review protocol - Rangarirai Matima; Claire van der Westhuizen; Crick Lund; Ferdinand C. Mukumbang (PLoS ONE, 2025)
Introduction Formulating and implementing mental health policy is foundational to public mental health. The implementation of mental health policy varies in low- and middle-income countries (LMICs), with some countries having better implementation outcomes than others. Low implementation poses challenges relating to addressing the high burden and wide treatment gaps of mental health conditions. While different implementation strategies are applied to implement mental health policy in different contexts, there is little knowledge of what category of strategies are being used and how and why their implementation produces varied outcomes. To this end, we propose to conduct a realist synthesis to explain how, why, for whom, and under what health system conditions certain policy implementation strategies work or not in LMICs. Methods and analysis This paper will detail the protocol on conducting a realist review of the literature on mental health policy implementation in LMICs. Realist reviews/syntheses are theory-driven reviews designed to formulate and test (confirm, refute, or refine) initial programme theories to explain how, why, for whom and under what contexts a programme, intervention or policy works as intended or not. Theory is built by exploring and abstracting context-mechanism-outcome (CMO) configurations in the data. These CMO configurations are identified through retroductive theorizing, a mechanism-centred approach to theory development. We will adopt these steps to guide the process of realist synthesis: i) identify the research question, clarifying the scope of the review and formulating the initial programme theory (ii) conducting background searches in PubMed, PsycINFO, Africa-Wide Information, African. Index Medicus (AIM), CINAHL and Scopus databases, and grey literature (iii) appraising the quality of studies and data extraction and (iv) synthesising data. Registration The review is part of a realist evaluation exploring mental health policy implementation in LMICs and is registered under PROSPERO (registration number: CRD42024580312). Findings will inform the development of initial mental health policy implementation programme theories explaining why and how mental health policy implementation in LMICs works.